Relationship between running spatiotemporal kinematics and muscle performance in well-trained youth female athletes. A cross-sectional study - Castillo-Domínguez, Alejandro; García-Romero, Jerónimo; Páez-Moguer, Joaquín; Ponce-García, Tomás; Medina-Alcántara, Francisco Miguel; Alvero-Cruz, José Ramón (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
The purpose of this cross-sectional study was to analyse the relationship of neuromuscular performance and spatiotemporal parameters in 18 adolescent distance athletes (age, 15.5 ± 1.1 years). Using the OptoGait system, the power, rhythm, reactive strength index, jump flying time, and jump height of the squat jump, countermovement jump, and eight maximal hoppings test (HT8max) and the contact time (CT), flying time (FT), step frequency, stride angle, and step length of running at different speeds were measured. Maturity offset was determined based on anthropometric variables. Analysis of variance (ANOVA) of repeated measurements showed a reduction in CT (p < 0.000) and an increase in step frequency, step length, and stride angle (p < 0.001), as the velocity increased. The HT8max test showed significant correlations with very large effect sizes between neuromuscular performance variables (reactive strength index, power, jump flying time, jump height, and rhythm) and both step frequency and step length. Multiple linear regression found this relationship after adjusting spatiotemporal parameters with neuromuscular performance variables. Some variables of neuromuscular performance, mainly in reactive tests, were the predictors of spatiotemporal parameters (CT, FT, stride angle, and VO). Rhythm and jump flying time in the HT8max test and power in the countermovement jump test are parameters that can predict variables associated with running biomechanics, such as VO, CT, FT, and stride angle. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.
Keywords: Ejercicio físico - Aspectos fisiológicos; Adolescent; Athletes; Athletic Performance; Biomechanical Phenomena; Cross-Sectional Studies; Female; Humans; Muscles